The Legitimacy of The Marriage of Husband and Wife Who Are Converts to Islam and the Implications for Their Descendants - H. M Umar (Yayasan Literasi Kita Indonesia, 2021)
Marriage in Indonesia has been regulated in laws and regulations that apply to all Indonesian people, namely the Marriage Law Number 1 of 1974.[1] In this Law as stated in Article 2 which reads that marriage is only valid, if it is carried out according to each religion and belief, then each marriage is recorded based on the applicable laws and regulations. The Jambi Religious Court as the executor of judicial power in the Jambi Religious High Court area has received 2 (two)cases isbat/ marriage ratifications for non-Muslim husbands and wives to become converts to get legal certainty from marriage before embracing Islam, namely the case with Number 14/Pdt.P /2017/PA Jmb on 01 February 2017 and the case with Number 64/Pdt.P/2019/PA Jmb on 09 August 2019. The reason for converting husbands and wives to submit isbat/ marriage ratification is because marriage before embracing Islam does not have a certificate marriage from the Civil Registry Office. So that the husband and wife of the converts filed a case isbat/ marriage ratification to the Jambi Religious Court to ask for the validity of their marriage. The Jambi Religious Court judge who tried the case, in his decision, granted the request and declared the marriage of a husband and wife to be converts to Islam without advocating remarriage. Even though the marital status of a non-Muslim husband and wife when they converted to Islam, the scholars were still debating until they were divided into two groups.